A new series of IDO1 inhibitors derived from microbial metabolites. (April 2023) - Zhu, Jingtong; Yu, Man; Shen, Wenbin; Ren, Xiao; Zheng, Haizhou; Mu, Yunlong; Lu, Xinhua; Zhai, Lili
Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1) is a rate-limiting enzyme catalyzing the metabolism of tryptophan along the kynurenine pathway, which has an effect on tumor immune escape, depression, inflammation, and neurodegenerative disease. Thus, IDO1 has become a promising therapeutic target in disease treatment, and IDO1 inhibitors have attracted much attention. In this study, we discovered a series of IDO1 inhibitors through high-throughput screening. The compounds belonged to angucyclinones. Compound 1 exhibited potent IDO1 inhibition in both enzymatic and cellular assays with IC50 values of 0.230 µM and 2.100 µM, respectively. Enzyme kinetics experiments revealed that Compound 1 was a reversible and uncompetitive inhibitor of IDO1. Furthermore, Compound 1 significantly reduced plasma kynurenine levels in a mouse model. This study identified potential IDO1 inhibitors for the development of new therapies in the treatment of multiple diseases. Graphical Abstract: ga1 Highlights: Several small molecule IDO1 inhibitors were screened from the library of microbial metabolites. The specific small-molecule inhibitors of IDO1 had not been reported. Compound 1 could inhibit IDO1 activity both in vitro and in vivo .